Mobile Learning Application With NativeScript Framework For Learning Material - Eliando Eliando; Ary Budi Warsito; Muhamad Yusup (CCIT Journal, 2020)
University is a place for the learning process and develops creativity in accordance with its own major program. There for an application is needed to fulfill those requirements. The application is not limited to the time and place as the result they could be used anywhere and anytime to support creativity between student and teacher. Mobile learning is one of the most suitable applications to support learning process and creativity development. Through Mobile Learning the teaching and learning process especially to acquire the teaching material can be easily access without limited time and place so communication between student and teacher can be more routine, efficient and can create learning process more focus and have an purposes balance with the lesson plan . Mobile learning application uses java script, css and native script framework that will make the next development for this application can be more easier, because nativescript framework already separate each module in accordance with its function. Finally, it facilitates the development of mobile application, so it is expected to be the first step in the mobile software future development.